OTONOMI DAN REFORMASI PENDIDIKAN - Abd Muis; Minhaji Minhaji (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
Autonomy and reformation in education is an improvement effort in the field of education. Educational reform has two basic characteristics: programmed and systemic. Programmed educational reform refers to the curriculum or program of an educational institution. Included in this programmed educational reform is innovation. Innovation is the introduction of new ideas, new methods or new tools to improve some aspects in the educational process. There are three education centers that are responsible for the implementation of education. They are family, school, and society. In the educational process, before getting to know the wider society environment and before getting guidance from the school environment, the student first gets guidance from the family environment.